Fundamental of Entrepreneurship (ENT 300) : Varietea / Marlini Dari ... [et al.] - Dari, Marlini; Mokhtar, Nur Asma; Abu Bakar, Nur Syuhada; Wan Amin, Sharifah Sharina; Abdul Halim, Intan Nur Haleeda (2016)
A business plan is a formal statement of a business goals, the reasons why they e believed attainable, and the plan for reaching those goals. Thus, it may also contains the background of the organization, such as the name, location, nature and other information about the company. Business plan may also target changes in perception and branding by the customers, clients, taxpayers or large communities. When creating a business to plan a new venture and to assume major changes in the future, a 3 to 6 months business plan is required. Business plan is also known as a detailed blueprint for activities needed to establish a business. For instance, details of a company's products and services, the coital required, the profits or losses and other details. Furthermore, business plan is also called a "yardstick" to a business, which means the owner of a company uses business plan as a tool to measure the success of their company through the goals and objectives in the business plan. Besides that, the business plan is also a tool for a company to obtain loans from a bank company to increase the capital contribution of a company in order to create a new venture of a business.